UJI TOKSISITAS EKSTRAK DAUN KENCUR (Kaempferia galanga L) DENGAN METODE BRINE SHRIMP LETHALY TEST (BSLT) - umar, linsih; hasan, hamsidar; sy pakaya, mahdalena (Indonesian Journal of Pharmaceutical Education, 2022)
One of the plants that has potential as medicine is kencur(Kaemoferia galanga L). Many studies have asserted that the rhizome of kencur is useful for bacterial infections, cough medicine, dysentery, cold, and stomachache. Therefore, the research aimed to identify the toxic effect of kencur leaf extract on artemia salina larvae applying the BSLT (Brine shrimp lethaly test) method. It employed three concentration treatments using 10 artemia salina larvae that died after 48 hours. Futher, it was calculated by LC50with probit analysis. The result of probit analysis revealed that the value of LC50from n-hexane extract was 96,13µg/mL, ethyl acetate extract was 98,22 µg/mL and methanol extract of kencur leaf was 156,06 µg/mL. The LC50 value of the extract was in the active category, with the value of LC50was lower than 1000 ppm.